Mitochondrial derivatives of culex quinquefasciatus (culicidae) spermatozoon : some new aspects evidenced by cytochemistry and image processing - Báo, Sônia Nair (1992)
Spermatozoa of the mosquito Culex quinquefasciatus have two mitochondrial derivatives of similar size and shape, containing a periodic matrix embedded by an amorphous region and surrounded by a membrane complex. The presence of cytochrome C oxidase activity was shown in the cortical zone. The use of the ethanolic-phosphotungstic acid technique suggests the presence of basic proteins in the paracrystalline structure. The analysis of the paracrystalline structure by digital image processing suggests that the cylindric-like subunits are empty structures and appear connected to each other by thin filaments. This approach showed that longitudinal filaments present an undulation disposition alongside the spermatozoon flagellum.